Islamic Ethics in Business Development: Principles and Frameworks for Entrepreneurial Success - Abdulkadir Abuabdin, Abubakar; Junaidu, Usman (International Journal of Islamic Economics and Governance, 2024)
This paper examines the influence that the Islamic ethics have on business development with special emphasis on entrepreneurial success. It contrasts Islamic ethics with the Protestant Work Ethic as a way of comparing the two on the best course of action when it comes to ethical matters in business. This study follows a conceptual research methodology to formulate a theoretical framework that connects the Islamic ethics comprising leadership, ethical reasoning, CSR, and entrepreneurship, to the business performance. Incorporation of the principles of the Islamic financing also forms part of the research framework for the study of sustainable and equitable business development. Preliminary outcomes show that Islamic ethics increase leadership usefulness, stakeholder credibility, and organizational efficiency by applying difficulties in practicing these norms in various cultural and geographical settings. In doing so, this research contributes to the literature of business ethics by presenting a faith-based approach that expands on the modern theories and gives constructive recommendations as it relates to applying Islamic principles for organizations today with a specific focus on SMEs.